Penerapan pemberdayaan masyarakat pelaku usaha lopek bugih melalui perlindungan hukum dan inovasi usaha Desa Palung Raya Kecamatan Tambang Kabupaten Kampar Riau - Emilda Firdaus; Firdaus Firdaus; Hengky Firmanda; Deby Kurnia; Sukamarriko Andrikasmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Palung Raya village has culinary potential that can be developed such as lopek bugih, lopek bugih which is a traditional food belonging to Kampar Regency, this meal is a meal of processed glutinous rice flour which is filled with grated coconut filled with sugar. The purpose of this activity is to support higher education programs through realizing the three principles of higher education as well as improving the economy of lopek bugih business actors. The method of application is provided by providing socialization and assistance in managing business legality, and creating the latest innovative taste of lopek bugih which so far only consists of one taste, these activities are carried out by directly involving business groups that have met the elements. The empowerment of lopek bugih business actors resulted in business legality and innovation in variations of lopek bugih.